Testing, Testing: Identifying Contemporary Analytics Practices in Digital Politics - Katherine Haenschen; Carl Cilke; Alise Boal (Journal of Quantitative Description: Digital Media)
Digital analytics in contemporary politics receives tremendous attention from the media and has been the focus of a great deal of research over the last two decades. However, the actual practices that characterize work in the field often fail to receive sufficient attention. This paper presents the results of a quantitative content analysis describing the contents of 39 digital analytics case studies reporting the results of 68 individual A/B tests to learn about testing practices as they exist at high levels in contemporary U.S. politics. We find an emphasis on email and website testing, predominantly focused on fundraising and engagement outcomes. Our findings illuminate the mundane but substantive impacts of testing, which are predominantly focused on improving fundraising and email performance. Since firms made these case studies publicly available on their website, they also serve as marketing materials. In this manner we can understand how the practice of analytics is sold to political organizations looking to engage in digital testing.